The role of publics and deliberation at the environmental science-policy interface - Wright-Arora, G; James, M; Troiano, M; Sidwell, N; Boyle, J; Barbrook-Johnson, P; Hirons, M (Agile Initiative, Oxford Martin School, 2024)
This discussion paper reviews the role of publics and deliberation at the environmental science-policy interface. We highlight two dominant ways to think of public(s), as either a homogenous whole, or as multiple and emerging around particular issues. The way we conceptualise public(s) will shape how and why public participation might be used. Environmental researchers and decision makers may choose to engage in public participation to steer environmental research towards more “democratic” outcomes, or to co-create new knowledge alongside publics. Deliberative democracy is one way of engaging the public through informed dialogue, reflection, and consideration of the conflicting ideas and values which are embedded in environmental challenges. We describe the foundations of deliberative democracy and some core complexities and considerations of deliberation, while assessing the role of different sources of knowledge in these processes. Public deliberation is no panacea for complex environmental challenges. It comes with risks including perpetuating a depoliticised image of global challenges as “solvable” through expert knowledge, rational conversation, and technological solutions. We attempt to articulate a path through these challenges towards a public participation which is reflexive and contextualised, and can contribute to building effective and just environmental knowledge and policy. We hope that the material in this discussion paper provides a constructive basis for precipitating reflections and discussions amongst researchers and other people involved in the production and use environmental research about their role in engaging with publics.